DINAMIKA DAN MODEL ARIMA PENAWARAN BERAS DI KABUPATEN SUKOHARJO SEBELUM DAN SELAMA PELAKSANAAN OTONOMI DAERAH (Periode Tahun 1994-2010) - Eka Dewi Nurjayanti; Darsono Darsono; Suprapti Supardi (MEDIAGRO, 2012)
The purpose of this research is to know the dynamics of suppling rice in era before and after regional autonomy in Sukoharjo Regency and to analyzed ARIMA model of them in Sukoharjo Regency on 2011 – 2015. The basic method applied in this research is analytical descriptive method. The research object is taken purposively, that is Sukoharjo Regency. The method of analysis data in this research is (1) Box-Jenkins (ARIMA) method with fourth steps, include identification, parameter estimation, diagnostic checking, and forecasting and (2) Chow Breakpoint Test. The result got from this research is the annual supply rice data have a fluctuation pattern with increase trend. It is not stationary and become stationary in first differencing. The result of parameter estimation judged that tentative model for the annual supply rice is ARIMA (0,1,1). The result of diagnostic checking judged that the best ARIMA model is ARIMA (0,1,1) with RMSE value is 5.186,376; R2 value is 0,850311; F-statistic value is 79,52704; and parameter of MA is significant because probabilistic value is less than 0,05. To suggest dummy variable with Chow Breakpoint Test showed that in 2000 was a period which affected annual supply and demand of rice, with F-statistic value is 3,033932 and this probability is significant. Regional autonomy not affected in supply and demand of rice. It is because rule of regional government less than main government in capital country. The result of forecasting annual supply of rice in 2011 – 2015 showed annual supply decreased. Keywords: supply, ARIMA, rice